A construção e validação de uma escala para medir o efeito manada dentro de restaurantes e similares - CANTO, Rodrigo Souza (2018)
This study aimed to develop a scale to measure the herd behavior in restaurants. This concept indicates a trend in part of the buying decisions: an individual costumer or a group of costumers have effective influence in habits like tastes, gestures and choices of another costumers. In the first moment, this work proposes a literature investigation about the pertinent factors of this phenomenon. In a second moment, in order to collect statistic data, a questionnaire composed of twenty-four affirmative sentences referring to herd behevior scenarios was developed. To verify the results over the behavioral trend it was used an exploratory factorial analysis. The KMO (Kaiser Meyer Olkin) test and the Bartllet test showing that the sample should be submitted to factorial analysis. The Principal Component extraction method and rotation by Varimax method, conjugated with the anti-image matrix or MSA - Measure of Sampling Adequacy was applyed. After the analysis, the Alpha of Cronbach factor was used to assure the reliability of the questionnaire. Therefore the statistical treatment grouped the factors into three constructs, here appointed as "Cognitive Comfort", "Heuristic and "Social Compliance”. This analysis lead to a better understanding of a relevant element in the discussion regarding the decision-making process for restaurant menu selection.